Solid Waste Disposal Habit of People of National Capital Region In India: Exploring Solid Waste Disposal Habits and Corporate Strategies in India's National Capital Region (Journal of Advances and Scholarly Researches in Allied Education, 2011)
It gives direction tocorporate values, corporate culture, corporate goals, and corporate missions.Under this broad corporate strategy there are typically business-levelcompetitive strategies and functional unit strategies. Refers to theoverarching strategy of the diversified firm. Such a corporate strategy answersthe questions of "which businesses should we be in?" and "howdoes being in these businesses create synergy and/or add to the competitiveadvantage of the corporation as a whole?" Business strategy refers tothe aggregated strategies of single business firm or a strategic business unit(SBU) in a diversified corporation. According to Michael Porter, a firmmust formulate a business strategy that incorporates eithercost leadership,differentiation, or focus to achieve a sustainable competitive advantage andlong-term success. These three rules are also known as Porter's three genericStrategies; this concept can be applied to any size or form of business. Porterconsidered this concept as tradeoff strategy and argued that a person orcompany must only choose ONE strategy or risk having no strategy at all.